Job Demands and Resources, Burnout, and Psychological Distress of Social Workers in China: Moderation Effects of Gender and Age - Xie, Xiaoxia; Huang, Chienchung; Cheung, Shannon P.; Zhou, Yuqing; Fang, Jingbo (Frontiers in Psychology, 2021)
Social work is a fast-growing profession in China, with the workforce numbering approximately 1.2 million in 2018. Studies have shown, however, that social workers in China experience high burnout rates and significant psychological distress. Analyzing data collected from 897 social workers in Chengdu, China, we applied the job demands and resources (JD-R) theory to examine the effects of JD-R on burnout and psychological distress in social workers, as well as whether these relations are moderated by gender and age. Results supported a dual process by which JD-R affected both social workers’ burnout and psychological distress through health impairment and motivation processes. Job demands (JD) were associated with high burnout and psychological distress. Meanwhile, job resources (JR) were associated with reduced burnout and psychological distress. Results indicated that JR had greater effects on burnout and distress than did JD. Women and younger professionals appeared to be affected most by JD and psychological distress. The findings support a need for interventions that buffer the effects of JD-R on burnout and psychological distress in social workers in China, focusing on women and younger professionals.